FAKE NEWS: THE CHALLENGE OF DIGITAL LITERACY IN DEALING WITH VISUAL DEEPFAKES ON FACEBOOK - Alamsyah, Aldi Alamsyah; Dian Lestari, Aghnia (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
Advances in artificial intelligence (AI) have significantly transformed the digital information ecosystem, particularly through the emergence of deepfake technology that enables highly realistic visual manipulation. This phenomenon poses serious challenges in distinguishing authentic from manipulated content, especially on social media platforms such as Facebook. This study aims to analyze the role of digital literacy in recognizing and responding to deepfake content, as well as to examine its patterns of dissemination and impact on public trust in visual information. This research employs a descriptive qualitative approach using in-depth interviews with experts from the Indonesian Anti-Slander Society (MAFINDO) and active Facebook users, complemented by digital observation of circulating deepfake content. The findings reveal that limited digital literacy significantly contributes to users’ inability to critically evaluate visual information, leading to the unintentional spread of misinformation, disinformation, and malinformation. Deepfakes are also strategically used for political propaganda and identity manipulation, further undermining trust in digital information. This study contributes to the literature by positioning digital literacy as a critical evaluative and ethical competency in addressing AI-driven visual disinformation within a platform-specific context. Strengthening digital literacy through targeted interventions is therefore essential to enhance users’ critical awareness and resilience against manipulated content in the digital environment.